Aspidistra saccata (Asparagaceae), a new species with erect stem from limestone areas in Guangxi, China - Huang, Xue-Yan; Peng, Yu-De; Nong, Dong-Xin; Huang, Bao-You; Yu, Li-Ying (Phytotaxa, 2022)
N/A